2018
DOI: 10.1007/s00442-018-4207-2
|View full text |Cite
|
Sign up to set email alerts
|

Aliens will provide: avian responses to a new temporal resource offered by ornithocorous exotic shrubs

Abstract: Frugivorous birds are able to track spatiotemporal changes in fruit availability. Food resource fluctuations, characteristic of seasonal environments, can be affected by the naturalization of exotic ornithocorous plants. In the mountain forest of central Argentina, invasive shrubs of the genus Pyracantha provide a new temporal resource that modifies fluctuations of natural resource availability because the invasives fructify in autumn-winter (largely uncoupled with the fruiting of native species). The contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…From our observations and remote camera-trap data, results support that birds are important potential seed dispersers (Díaz Vélez et al 2018, Vergara-Tabares et al 2018). This showed that bird species are effective seed dispersers of P. angustifolia.…”
Section: Discussionsupporting
confidence: 67%
“…From our observations and remote camera-trap data, results support that birds are important potential seed dispersers (Díaz Vélez et al 2018, Vergara-Tabares et al 2018). This showed that bird species are effective seed dispersers of P. angustifolia.…”
Section: Discussionsupporting
confidence: 67%
“…2a). An additional factor that may be operating in the pattern of fruit removal, is the abundance of seed disperser birds which was shown to be similar among invasion situations in a previous study (Vergara-Tabares et al 2018a). As the increase in frugivory by birds was observed only during the overlapping period at invaded sites, the facilitation of the fruit removal of the native tree would be driven by an increase in seed dispersers in response to overall fruit supply (Gleditsch and Carlo 2011).…”
Section: Does Invasion By Fleshy Fruited Species Disrupt or Facilitate Native Seed Dispersal Mutualisms?mentioning
confidence: 74%
“…Four of the sites are invaded by Pyracantha angustifolia (Rosaceae) and Pyracantha atalantoides , species native to eastern Asia which have established mainly on stream margins but rarely on ravine slopes (Vergara‐Tabares unpubl.). Both Pyracantha species produce fruit during early autumn to late winter (September), when fruit resources from native plant species are scarce or absent (Vergara‐Tabares et al 2016, 2018a). Pyracantha covered less than 20% (hereafter ‘low invasion') in two invaded sites (Los Hornillos: 31°54′6.88″S, 64°58′35.24″W; Las Calles: 31°51′1.68″S, 64°56′18.37″W) and between 30 and 40% (‘high invasion') in other two invaded sites (La Población: 32°3′32.12″S, 64°59′57.08″W; San Javier: 32°1′36.97″S, 64°59′41.70″W).…”
Section: Methodsmentioning
confidence: 99%
“…(iv) Firethorn ( Pyracantha angustifolia ) is an evergreen and thorny shrub from China whose fleshy fruits are dispersed by birds (Vergara‐Tabares et al . , ). (v) Chinaberry ( Melia azedarach ) is a deciduous tree from Southeast Asia probably dispersed by birds and bats (Mabberley ; Voigt et al .…”
Section: Methodsmentioning
confidence: 99%
“…, ; Vergara‐Tabares et al . ), with the dispersal stage overlapping with the fire season (Giorgis et al . ; Argañaraz et al .…”
Section: Introductionmentioning
confidence: 99%